2016
DOI: 10.1111/vde.12306
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study comparingin vitroefficacy of topical preparations against veterinary pathogens

Abstract: Chlorhexidine, NaOCl and HOCl demonstrated low MBCs against tested organisms, suggesting potential in vivo efficacy. The selection of an appropriate antimicrobial agent, however, cannot be based exclusively upon MBC/MFC data; other factors should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…However, a previous study evaluated the mean bacterial and fungicidal concentrations (MBC and MFC, respectively) of a shampoo containing 3% chlorhexidine and 0.5% climbazole (DOUXO Pyo® Shampoo, Sogeval; Laval Cedex, France) against S . pseudintermedius in vitro and found higher MBCs and MFCs when compared to a 3% chlorhexidine solution alone . That study leads the present authors to believe that climbazole and chlorhexidine may not be synergistic; however, additional studies are needed to further evaluate this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…However, a previous study evaluated the mean bacterial and fungicidal concentrations (MBC and MFC, respectively) of a shampoo containing 3% chlorhexidine and 0.5% climbazole (DOUXO Pyo® Shampoo, Sogeval; Laval Cedex, France) against S . pseudintermedius in vitro and found higher MBCs and MFCs when compared to a 3% chlorhexidine solution alone . That study leads the present authors to believe that climbazole and chlorhexidine may not be synergistic; however, additional studies are needed to further evaluate this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Uri and others (2016) reported that the minimal inhibitory concentration (MIC) of MDR (multiple drug resistant) PA was 0.94 g/L compared to the recommended concentration of 0.5 g/L. [23] The wipes in our study contain 0.3% (3 g/L) chlorhexidine, which is lower than that in many topical products (typically 2–4%; 20-40 g/L). Nevertheless, in vitro inhibition has been demonstrated with a 0.15% chlorhexidine ear cleaner, and chlorhexidine has MIC and minimal bactericidal concentrations (MBCs) of 0.6–10 mg/L against the ESBL-EC and 5–10 mg/L against the PA isolates used in this study (data submitted for publication).…”
Section: Discussionmentioning
confidence: 68%
“…MICs for chlorhexidine against ESBL-EC in human clinical isolates was determined as < 1-2 mg/L [26, 27] and in avian isolates as 0.5-1 mg/L. [27] MBCs of ESBL-EC were 7.32 mg/L (3 min incubation) to 1.83 mg/L (10 min incubation) with a 4% chlorhexidine product, and 468.75 mg/L (3 and 10 min incubations) with a 3% chlorhexidine/0.5% climbazole product [23]. These additional studies have determined MIC/MBC comparable to the our submitted study.…”
Section: Discussionmentioning
confidence: 99%
“…31,33 An in vitro pilot study evaluating the minimum bactericidal and fungicidal concentrations (MBC/MFC) of seven antiseptics against veterinary pathogens at 3 and 10 min postapplication reported that hypochlorous acid had significantly lower MBC and MFC compared to sodium hypochlorite. 33 In another pilot study, 19 dogs with superficial pyoderma were treated with either a saline spray (11 of 19) or 0.011% veterinarylabelled hypochlorous acid spray (eight of 19) twice daily for 4 weeks. No statistically significant differences in lesion scores, polymorphonuclear leucocyte counts and intracellular cocci counts were reported between groups.…”
Section: Discussionmentioning
confidence: 99%